Knowledge management tools and techniques - Foo, Schubert (Pearson Prentice Hall, 2007)
This book introduces a range of frameworks to classify knowledge management (KM) tools, examines these different classes of tools in detail by answering the 4Ws (What-Why-Where-Who) and how questions, addressing the selection, implemention and evaluation issues associated with these tools.